A high-voltage all-solid-state lithium-ion battery with Li–Mn–Ni–O and silicon thin-film electrodes. (June 2015) - Chen, Y.; Tang, Z.; Yang, S.; Wang, Y.; Chua, D.
<x content-type="archive" xml:space="preserve">Abstract</x> All-solid-state thin-film lithium-ion batteries are deemed a promising replacement for liquid electrolyte-based Li-ion batteries owing to their superior cycle life, compact structure, high energy and power densities with an extremely low self-discharge rate. However, the state-of-art all-solid-state Li-ion batteries mainly use thermal-evaporated lithium metal as anode, which considerably undermines their cost-effectiveness and also raises safety concerns of Li explosion. In this study, a spinel Li–Ni–Mn–O/lithium phosphorus oxynitride (LiPON)/Si-based all-solid-state Li-ion battery has been successfully developed using sputter-deposition technique. This Li-free all-solid-state Li-ion battery exhibited a high cut-off voltage of 4.55 V and superior cycling stability in a wide potential range from 3.0 to 4.55 V. The highest specific capacity of the spinel Li–Ni–Mn–O/LiPON/Si-based all-solid-state Li-ion battery achieved so far is 40 μAh cm− 2 and further optimisation is currently under way.